Analisis Suseptibilitas Magnetik Tanah Perkebunan Apel di Kecamatan Pujon Kabupaten Malang: Indonesia - Rikardus Feribertus Nikat; Ninik Munfarikha (Universitas Islam Negeri Alauddin Makassar, 2024)
This research aims to analyze the magnetic susceptibility value of apple plantation soil to determine the magnetic value as a representation of the heavy metal content on the soil surface due to pesticide residues. This research was carried out by taking samples at nine predetermined points. Each sample was taken from the ground surface at varying depths of 10 cm, 20 cm, and 30 cm. The total number of samples was as large as samples and tested for magnetic susceptibility values ​​at the central laboratory of the State University of Malang. The average value of low-frequency magnetic susceptibility per mass χ_LF is 673.642 x 10-8m^3/kg, and the average value of high-frequency magnetic susceptibility per mass χ_HF is 649.0473 x 10-8 m^3/kg. The average frequency-dependent magnetic susceptibility value χ_FD per mass is 2.04%. The surface soil of plantations contains high concentrations of ferrimagnetic minerals in the form of magnetite and maghemite with grain properties in the form of multi-domain (MD) and superparamagnetic (SP).